Precision Analysis of Solar Astrometric Positions from the JPL DE431 Ephemeris. Issue 4 (June 2021) - Ma, Lihua; Wang, Xiaolan; Pang, Feng; Kong, Ting
Abstract: The DE (Development Ephemeris) series of planetary ephemeris released by NASA's Jet Propulsion Laboratory (JPL) have been widely used in deep-space navigation, interplanetary exploration, analysis and reduction of high-precision astronomical observations, and calibrations of gravitational theories etc. This work takes solar astronomic positions as an example to analyze precision of the JPL DE431 planetary ephemeris data. The results show that the DE431 ephemeris has high precision, which can be guaranteed within 0.08 milliarcseconds (mas), and can be used to carry out high-precision calculation of planetary positions.